1998
DOI: 10.1215/03616878-23-3-455
|View full text |Cite
|
Sign up to set email alerts
|

Does Removing Certificate-of-Need Regulations Lead to a Surge in Health Care Spending?

Abstract: This study assesses the impact of certificate-of-need (CON) regulation for hospitals on various measures of health spending per capita, hospital supply, diffusion of technology, and hospital industry organization. Using a time series cross-sectional methodology, we estimate the net impact of CON policies on costs, supply, technology diffusion, and industry organization, controlling for area characteristics, the presence of other forms of regulation, such as hospital rate-setting, and competition. Mature CON pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 27 publications
2
86
0
Order By: Relevance
“…The strong consensus of this literature is that hospital CON is associated with similar or higher inpatient costs (Conover and Sloan 1998;Antel et al 1995;Ohlhausen 2015). Less attention has been directed toward the impact of hospital CON on hospital quality, with some studies suggesting improved quality for complex inpatient procedures (Vaughan-Sarrazin et al 2002), but lower quality for more routine hospital care (Stratmann and Wille 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The strong consensus of this literature is that hospital CON is associated with similar or higher inpatient costs (Conover and Sloan 1998;Antel et al 1995;Ohlhausen 2015). Less attention has been directed toward the impact of hospital CON on hospital quality, with some studies suggesting improved quality for complex inpatient procedures (Vaughan-Sarrazin et al 2002), but lower quality for more routine hospital care (Stratmann and Wille 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that certificate of need (CON) programs have been ineffective in controlling hospital costs (Lanning, Morrisey, and Ohsfeldt 1991;Conover and Sloan 1998). However, many have argued that such programs have limited the growth of the nursing home industry, and thereby limited state Medicaid expenditures.…”
Section: The Effects Of Con Repeal On Medicaid Nursing Home and Long-mentioning
confidence: 99%
“…Over the years there have been several attempts to examine the effects of nursing home CON (Feder and Scanlon 1980;Birnbaum et al 1982;Lee, Birnbaum, and Bishop 1983;Harrington and Swan 1987;Harrington et al 1997;Conover and Sloan, 1997;Miller et al 2001). Most have focused on either the effects of CON on bed capacity or the effects of bed capacity on Medicaid expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…The definitions and sources of the variables associated with each covariate vector are described in Table 1 h State data based on data from Conover and Sloan (1998;. ( share of Medicare and Medicaid inpatient days (MCARE; MCAID).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the impact of CON programs consistently have found the programs to be ineffective at controlling costs and enhancing access, and in some cases have been shown to increase costs (Sloan 1988;Lanning, Morrisey, and Ohsfeldt 1991;Antel, Ohsfeldt, and Becker 1995;Conover and Sloan 1998). The U.S. experience with airline regulation is the opposite.…”
mentioning
confidence: 99%